Generation of a Transgenic Zebrafish Model for Pancreatic Beta Cell Regeneration - Pourghadamyari, Hossein; Rezaei, Mohammad; Basiri, Mohsen; Tahamtani, Yaser; Asgari, Behrouz; Hassani, Seyedeh-Nafiseh; Meshkani, Reza; Golmohammadi, Taghi; Baharvand, Hossein (Galen Medical Journal, 2019)
Background: Diabetes is a major worldwide health problem. It is widely accepted that the beta cell mass decreases in type I diabetes (T1D). Accordingly, beta cell regeneration is a promising approach to increase the beta cell mass in T1D patients. However, the underlying mechanisms of beta cell regeneration have yet to be elucidated. One promising avenue is to create a relevant animal model to explore the underlying molecular and cellular mechanisms of beta cell regeneration. The zebrafish can be considered a model in beta cell regeneration studies because the pancreas structure and gene expression pattern are highly conserved between human and zebrafish. Materials and Methods: In this study, the Tol2 transposase was exploited to generate a Tg(Ins:egfp-nfsB) zebrafish model that expressed a fusion protein composed of enhanced green fluorescent protein (EGFP) and nitroreductase (NTR) under control of the Ins promoter. Results: Metronidazole (MTZ) treatment of Tg(ins:egfp-nfsB) zebrafish larvae led to selective ablation of beta cells. Proof-of-concept evidence for beta cell regeneration in the transgenic larvae was observed two days after withdrawal of MTZ. Conclusion: This study suggests that the Tg(ins:egfp-nfsB) zebrafish can be used as a disease model to study beta cell regeneration and elucidate underlying mechanisms during the regeneration process. [GMJ.2019;8:e1056]